ANALISIS RASIO SOLVABILITAS PADA RUMAH SAKIT UMUM HAJI MEDAN UNTUK MENILAI KINERJA KEUANGAN - Pane, Dini Azlina; Kamilah, Kamilah; Jannah, Nurul (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to find out how the solvency of Haji Medan General Hospital is to assess financial performance. The research method uses financial report data for the 2018 and 2019 periods. This research uses a descriptive qualitative method by conducting interviews, documentation, and literature. I tested the data using the Debt to Assets Ratio and the Debt to Equity Ratio. In this study, researchers found that the financial performance of the Medan Hajj General Hospital based on the solvency ratio of the condition of the company's financial performance was not good because the results were far below the ratio standards of the financial industry. Keywords: Financial Statements, Financial Performance